Pengaruh Literasi Keuangan terhadap Perilaku Konsumtif Siswa Kelas XII SMA Negeri 15 Surabaya - Andika Pratama Wijaya; Siti Nurhaliza Putri; Muhammad Rizky Saputra (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the effect of financial literacy on the consumptive behavior of twelfth-grade students at SMA Negeri 15 Surabaya. Financial literacy is an important aspect in shaping individuals' ability to manage their finances wisely, especially among adolescents who are vulnerable to consumptive behavior due to environmental influences and technological developments. The research method used is a quantitative approach with a survey design. The sample consisted of 120 students selected using purposive sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability. The data analysis technique employed simple linear regression to determine the relationship between financial literacy and consumptive behavior variables. The results showed that financial literacy has a negative and significant effect on students' consumptive behavior. This means that the higher the level of students' financial literacy, the lower their tendency to engage in consumptive behavior. Conversely, a low level of understanding of financial management encourages students to make purchases not based on their needs. These findings indicate the importance of early financial literacy education as a preventive effort to reduce consumptive behavior among students. This study is expected to serve as a reference for schools and policymakers in designing effective and sustainable financial education programs.